Analysis of sexual activity in pregnant women without obstetric risk attending public hospitals in Lima, Peru - Guibovich Mesinas, Alex (2015)
Objective: To know the characteristics of sexual activity in pregnant women without obstetric risk who attend public hospitals in Lima. Material and Methods: exploratory, multicenter, descriptive and cross-sectional study, conducted during the first half of 2014 in 9 public hospitals in Lima. The sample was made up of pregnant women without obstetric risk who attended the outpatient clinic of obstetric departments. Anon-probabilistic model is used for convenience. An expert validated survey was conducted on patients who voluntarily agreed to participate and signed the informed consent. The information was analyzed using STATA 21 software. Results: 1991pregnant women answered the survey, 924 (46.4%) were between 15 and 25 years, most were married, and Catholic (81.8%) and 1380 (69.3%) were born in Lima. Most had several previous pregnancies (46.3%), with term pregnancy and 86.3% informed they had no pre-term infants. 1347(67.6%) had vaginal delivery. The frequency of sexual acts, sexual desire, the response pattern and the fear of exercising sexual intercourse decreased at higher gestational age. Fear of sex acts increased from 12.6% to 76.2% in the third trimester. Most informed of a lack of orgasm during intercourse (42.8%).The position for intercourse went from "him on her" in the first trimester to "sideways" during the third trimester, with statistical significance. Conclusion: sexual activity in pregnant women of Metropolitan Lima tend to decrease in frequency, desire, and response cycle. The "sideways" position was the most often used in the third trimester.